2013
DOI: 10.1371/journal.pone.0074931
|View full text |Cite|
|
Sign up to set email alerts
|

Age, Sex, and Telomere Dynamics in a Long-Lived Seabird with Male-Biased Parental Care

Abstract: The examination of telomere dynamics is a recent technique in ecology for assessing physiological state and age-related traits from individuals of unknown age. Telomeres shorten with age in most species and are expected to reflect physiological state, reproductive investment, and chronological age. Loss of telomere length is used as an indicator of biological aging, as this detrimental deterioration is associated with lowered survival. Lifespan dimorphism and more rapid senescence in the larger, shorter-lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 43 publications
2
42
1
Order By: Relevance
“…cohort effects). This is in accordance with previous studies on mammals, lizards and birds [25][26][27][55][56][57][58][59][60], which have shown increased telomere shortening in response to suboptimal environmental conditions. For example, Mizutani et al [60] showed that in black-tailed gulls (Larus crassirostris), the rate of change in telomere length mainly differed with respect to year, and they attributed this to the consequences of El Niñ o events and the Great Japan Earthquake on food availability.…”
Section: Discussionsupporting
confidence: 93%
“…cohort effects). This is in accordance with previous studies on mammals, lizards and birds [25][26][27][55][56][57][58][59][60], which have shown increased telomere shortening in response to suboptimal environmental conditions. For example, Mizutani et al [60] showed that in black-tailed gulls (Larus crassirostris), the rate of change in telomere length mainly differed with respect to year, and they attributed this to the consequences of El Niñ o events and the Great Japan Earthquake on food availability.…”
Section: Discussionsupporting
confidence: 93%
“…Although TL (and rates of change) have previously been shown to differ by sex and breeding colony in many species (reviewed in Barrett & Richardson 2011) including the thick-billed murre (Young et al 2013), such differences were not found in this study. However, male murres spend the first weeks after colony departure with the fledgling, diving intensely to supply both chick and self (Elliott & Gaston 2014).…”
Section: Overwinter Behaviors and δTlcontrasting
confidence: 62%
“…ΔTL was usually calculated from 1 yr to the following year, but in 4 cases telomeres were re-sampled after 2 yr; in these cases, ΔTL was divided by 2 to indicate mean annual change. In addition to wintering variables, we include other measures likely to affect migration and TL: year (of global location sensing deployment, first capture), sex (Young et al 2013(Young et al , 2015, colony (Young et al 2015), body size (Barrett et al 2013, Orben et al 2015, body mass, and the annual change in body mass. Twenty-three birds had complete data and could be used in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…individuals. The majority of studies were performed on long-lived birds while telomere length was measured only twice in the entire lifespan of an individual (Hall et al 2004;Pauliny et al 2006;Bize et al 2009;Bauch et al 2013;Young et al 2013), but see Salomons et al (2009), Barrett et al (2013) and Asghar et al (2015). To our knowledge short-lived species have been considered in longitudinal studies of telomere dynamics only recently (Heidinger et al 2012;Asghar et al 2015); therefore a between-species comparative study of lifespan-dependent telomere erosion on an intra-individual level was not possible until now.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%